Pemberdayaan Masyarakat Desa Tahunan Baru Kabupaten Pacitan melalui Optimalisasi Produk Biofarmaka - Susanti, Ari Diana; Mochtar, Achmad Wahyu; Pristiwijayani,, Ana; Taukida,, Arzaq; Lanyazzahra, Athifah; Lestari, Dea Saskya Eka Puji; Timur, Ilyas Pramudya; Naaifah, Mega Isti; Fajriah, Raihana; Meisari, Rizka (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2022)
The territory of Indonesia consists of various types of graphic conditions with various prosperities that arevery potential to be developed. One of them is the potential of biopharmaceuticals products in Pacitan Regency, precisely in Tahunan Baru Village, Tegalombo District. Packaging and marketing ofbiopharmaceutical products is still a basic problem that will be solved through the Sebelas Maret University's Student Community Program or 'Kuliah Kerja Nyata' (KKN) for the July-August 2022 period.Initial surveys show that packaging has not yet become an important aspect to attract market interest. Crucial information related to the product has not been included in the packaging design, such as product identity, expiration date, and composition. From the marketing aspect, product sales are still in the conventional way. To support the optimization of biopharmaceuticals products in terms of packaging and marketing, the programs are carried out in the form of human resource development, mapping and digitising MSMEs, ginger candy, rebranding, labelling, and digital marketing training. Implementation of activities using face-to-face methods both individually and in groups in the form of socialisation, discussion and demonstration or direct practice.